Examination of Performance Levels of Wheelchair Basketball Players Playing in Different Leagues - Mehmet Fatih Yüksel; Tarık Sevindi (MDPI AG, 2018)
This research was conducted to examine the anthropometric and biometric features of the elite wheelchair basketball players in different league levels, and to evaluate them with regards to field tests particular to wheelchair basketball. A sample of 21 male players volunteered to participate in the research with similar classification points, 12 of whom were from Turkey Wheelchair Basketball First League and 9 of whom were from the Second League. Anthropometric measurements, biometric features of the players and their skill test scores particular to wheelchair basketball were detected. The anthropometric measurements were taken over dominant extremity. SPSS 21.0 program was used in the analysis of the data, and minimum, maximum, arithmetic mean, and standard deviation values were determined. Intergroup differences were determined with Mann-Whitney U analysis. Significance level was admitted as p < 0.05. As a conclusion, it was determined that wheelchair basketball players had similar anthropometric features in the First and Second League levels, and that there was no difference based on the league level they were playing, and moreover, that bio-motor features and skills particular to wheelchair basketball were decisive on the levels of the leagues the players were taking part.